Keberlanjutan Ekonomi dalam Perspektif Hukum: Analisis Regulasi Environmental, Social, and Governance di Indonesia - Kossay, Methodius; Putra, Rengga Kusuma; Idris, Maulana Fahmi (Universitas Sains dan Teknologi Komputer, 2025)
The implementation of Environmental, Social, and Governance (ESG) regulations in Indonesia is still in its developmental stage and faces several challenges in enforcement and compliance. Compared to developed countries, Indonesia's ESG framework lacks strong incentives and adequate regulatory oversight, leading to inconsistencies in corporate adherence. This study aims to analyze the effectiveness of ESG regulations in Indonesia from a legal perspective and evaluate their impact on corporate compliance. A normative juridical approach was used, supplemented by case studies of companies that have implemented ESG principles. Data were collected through document analysis of regulatory frameworks, sustainability reports, and interviews with key stakeholders. The findings indicate that while the number of companies adopting ESG practices has increased significantly from 45 in 2018 to 675 in 2023, only 38% fully comply with ESG standards. Moreover, statistical analysis reveals a strong correlation (r = 0.78, p < 0.05) between regulatory strictness and corporate adherence. Weak enforcement mechanisms and the voluntary nature of ESG reporting remain major obstacles to effective implementation. The study also highlights that firms integrating ESG principles tend to attract more investment and demonstrate better financial stability. The findings contribute to the ongoing discourse on ESG regulation by emphasizing the need for policy reforms, including stricter enforcement, standardized reporting mechanisms, and economic incentives to enhance compliance. This research provides a foundation for future comparative studies on ESG regulation and suggests integrating technology-based monitoring tools such as blockchain and artificial intelligence to improve corporate accountability and sustainability practices.